Gradience in L2 procesing: the importance of the non-protoypical - Geld, Renata (2007)
According to cognitive grammar, one of the fundamental assumptions concerning the nature of language is that “ much in language is a matter of degree” (Langacker, 1987:14). The issue of discreteness is discussed in terms of the following aspects of linguistic categories and linguistic relationships: (a) the inadequacy of simple categorical judgments, (b) doubtful cognitive validity of the criterial-attribute model, (c) the inappropriateness of applying a sharply dichotomous organization on gradient phenomena, and (d) the question whether an integrated system is adequately described componentially (Langacker, 1987). The aim of this paper is to discuss the importance of gradience in L2 processing and the implications of the traditional grammatical/ungrammatical dichotomy prevalent in teaching a second language. We wish to claim that traditional textbooks and grammars do not accommodate for learners’ judgments of “ well-formedness along a continuous scale of values” (Langacker 1987: 15) but encourage assessments based on a variety of plus/minus features in the form of lists of rules related either to the form or the function of a particular linguistic structure. Furthermore, we claim that, in case of the present perfect tense, textbooks fail to stress the important distinction between the time frame or the time sphere (Radden and Dirven, 2007), which includes both the event and the speech event, and adjuncts of time that locate the event at some point anterior to the reference time. Finally, we wish to show that even in the case of very proficient learners, non-prototypical instances are not integrated in language teaching material and syllabus, which results in students’ incapacity to go beyond the explicitly learned rules, make personal inferences about non-prototypical cases, and thus recognize the most schematic and unifying schema that keeps the category together. In order to support our hypotheses, first we analyzed the most frequently used English textbooks in Croatian schools to demonstrate the content and sequence of teaching the present perfect, and then we conducted research into strategic construal (Geld 2006) of two non-prototypical uses of the present perfect tense. The paper analyzes the answers obtained from 175 English majors and discusses the results that support the above stated hypotheses. It has been found that even proficient learners of English largely rely on the learned rules and in doing so fail to (re)consider contextual clues that point to a particular example being construed as a valid member of the present perfect category.